2004
DOI: 10.1345/aph.1e194
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation: A Pilot Study of the Effects on Health-Related Quality of Life and Perceived Work Performance One Week into the Attempt

Abstract: This pilot study found that, generally, HRQoL changes one week into a smoking cessation attempt. Smokers with higher addiction have lower HRQoL when they begin their cessation attempt, while smokers with lower addiction have greater change in HRQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…While both groups experience significant improvements in self‐control, only the light smoker group reported a significant improvement in sleep, cognitive functioning, and anxiety. Overall, the light smoker group had greater improvements in their QoL during this first week . In another study, large differences between ex‐smokers and current heavy smokers were found.…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…While both groups experience significant improvements in self‐control, only the light smoker group reported a significant improvement in sleep, cognitive functioning, and anxiety. Overall, the light smoker group had greater improvements in their QoL during this first week . In another study, large differences between ex‐smokers and current heavy smokers were found.…”
Section: Methodsmentioning
confidence: 90%
“…As stated in the introduction, smoking cessation is strongly associated with an overall improvement in general health ( p = .01), mental health, physical health and activity limitations . QoL data helps to better understand how an individual experiences these changes.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…(5,14,(16)(17)(18) In our study, only subjects who self-reported cessation and presented low exhaled CO levels (confirmed abstinence) were classified as quitters.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, emotionality also accounted for more than twice the variance found for the same emotionality factor in the initial validation sample of nontreatment-seeking smokers, and this factor loaded substantially higher on three of four items (3, 10, and 12) than either the FTCQ and TCQ. There is signifi cant worsening of anxiety related to smoking cessation ( Erickson, Thomas, Blitz, & Pontius, 2004 ), and post-hoc analysis indicated that anxiety was the most prominent DSM-IV withdrawal symptom associated with craving in anticipation of relief from withdrawal or negative mood ( r = .35, p < .001).…”
Section: Discussionmentioning
confidence: 99%